Human Cytomegalovirus Fcγ Binding Proteins gp34 and gp68 Antagonize Fcγ Receptors I, II and III - Corrales Aguilar, Eugenia (2014)
Human cytomegalovirus (HCMV) establishes lifelong infection with recurrent episodes of virus production and shedding despite the presence of adaptive immunological memory responses including HCMV immune immunoglobulin G (IgG). Very little is known how HCMV evades from humoral and cellular IgG-dependent immune responses, the latter being executed by cells expressing surface receptors for the Fc domain of IgG (FcγRs). Remarkably, HCMV expresses the RL11-encoded gp34 and UL119-118-encoded gp68 type I transmembrane glycoproteins which bind Fcγ with nanomolar affinity. Using a newly developed FcγR activation assay, we tested if the HCMV-encoded Fcγ binding proteins (HCMV FcγRs) interfere with individual host FcγRs. In absence of gp34 or/and gp68, HCMV elicited a much stronger activation of FcγRIIIA/CD16, FcγRIIA/CD32A and FcγRI/CD64 by polyclonal HCMV-immune IgG as compared to wildtype HCMV. gp34 and gp68 co-expression culminates in the late phase of HCMV replication coinciding with the emergence of surface HCMV antigens triggering FcγRIII/CD16 responses by polyclonal HCMV-immune IgG. The gp34- and gp68-dependent inhibition of HCMV immune IgG was fully reproduced when testing the activation of primary human NK cells. Their broad antagonistic function towards FcγRIIIA, FcγRIIA and FcγRI activation was also recapitulated in a gain-of-function approach based on humanized monoclonal antibodies (trastuzumab, rituximab) and isotypes of different IgG subclasses. Surface immune-precipitation showed that both HCMV-encoded Fcγ binding proteins have the capacity to bind trastuzumab antibody-HER2 antigen complexes demonstrating simultaneous linkage of immune IgG with antigen and the HCMV inhibitors on the plasma membrane. Our studies reveal a novel strategy by which viral FcγRs can compete for immune complexes against various Fc receptors on immune cells, dampening their activation and antiviral immunity.